A spectrum of approaches to health information interaction: From avoidance to verification. (26th October 2019) - Costello, Kaitlin L.; Veinot, Tiffany C.
Abstract: People respond to illness in a range of ways, and take different approaches to engaging with health information throughout the course of their illness. This study describes and explains the variety of approaches to health information interactions made by patients on hemodialysis. Ethnographic observations (156 hours) were conducted in three hemodialysis clinics, and semistructured interviews about health information were held with 28 patients. Demographic data were collected. Data were analyzed qualitatively. We found a spectrum of five approaches to health information: avoiders, who close themselves off from health information; receivers, who encounter information in the dialysis clinic but do not seek it out; askers, who only pose questions about health to their healthcare providers but otherwise do not seek; seekers, who actively look for health information both in and out of the clinic; and verifiers, who seek information and triangulate it among multiple sources. Trust in healthcare providers and coping sociality differed across approaches. The findings indicate that health information should be provided to patients using strategies tailored to their preferences and existing approaches to information interaction.